The Effects of Residual Stress and HAZ on Fatigue Crack Growth in MIG Welded 2024 and 7150 Aluminium - Lin, J.; Ganguly, Supriyo; Edwards, Lyndon; Irving, Phil E. (Cranfield University, 2003)
The effect of weld residual stress, and hardness profile on fatigue crack propagation in MIG welded 2024 and 7150 aluminium joints was studied. Residual stress fields in the weld were measured using neutron diffraction. Tests were performed using a range of mean stresses and on different starting defect shapes. It was found that fatigue crack propagation in weld metal and HAZ is influenced by crack morphology and also the distribution of residual stress and hardness. Control of these parameters will optimise damage tolerance capability in welded safety critical structures.